Birth Techniques Ball On The Intensity Of Labor Pain In Mothers Giving Birth In The First Stage Of Active Phase - Dia Rejeki Utami; Djunaedi Djunaedi (Asosiasi Guru dan Dosen Seluruh Indonesia, 2026)
Labor pain is a physiological experience experienced by women during labor due to uterine contractions and cervical dilation. Labor pain management can be carried out pharmacologically or non-pharmacologically. One non-pharmacological method that can be used is the birth control technique. ball. Birth The birth ball is an exercise using a special ball that helps laboring mothers perform pelvic movements, increasing comfort and reducing pain intensity. This study aims to analyze the effectiveness of this birth ball technique. The effect of ball on the intensity of labor pain in mothers in the first stage of labor during the active phase. The study used a quasi-experimental design with a pretest - posttest approach. without control group. A sample of 30 mothers giving birth was selected using a purposive sampling technique. Pain intensity was measured using a Numeric Rating Pain Scale (NRS). The results showed that the average pain score before the intervention was 7.3 ± 1.1 and after the intervention it became 5.1 ± 1.0 with a p value < 0.001. It was concluded that the birth control technique Ball is effective in reducing the intensity of labor pain in the first active phase.